Determinants of Consumer Purchase Intention in Teaching Factory-Based Business Units: An Empirical Analysis of Price Perception, Product Quality, and Promotion within Vocational Education - Ayu Wiwin, Ni Komang; Widiastini, Ni Made Ary; Rahmawati, Putu Indah (Dinasti Publisher, 2026)
In the landscape of modern vocational education, the transformation of Vocational High Schools (SMK) into Regional Public Service Agencies (BLUD) through the Teaching Factory (TEFA) mechanism necessitates the adoption of professional business management practices. This study aims to deconstruct the factors influencing student purchase intention within school-based retail units, utilizing Smensimart at SMKN 1 Singaraja as a case study. Employing a quantitative approach with a causal research design, this study involved 190 respondents selected via purposive sampling. Data were analyzed using multiple linear regression following rigorous validity, reliability, and classical assumption tests. The findings reveal that price perception, product quality, and promotion simultaneously exert a significant influence on purchase intention, with a coefficient of determination () of 69.7%. Partially, product quality emerged as the strongest predictor (β=0.401), followed by price perception (β=0.394) and promotion (β=0.297). These findings challenge the traditional assumption that students are exclusively price-sensitive consumers, suggesting instead that they are rational consumers who prioritize value and quality. This article contributes theoretically to the educational marketing literature and offers practical implications for school business unit managers in designing robust marketing mix strategies.